The intervention of the state in financial stability: The experience of KU 1982 – 2021 - Altami, Saud Naser Falah (Journal of Economic, Administrative and Legal Sciences, 2022)
The financial and economic crises that occurred in the State of Kuwait between 1982 and 2021 have shown that the role and responsibilities of the State have varied in meeting economic challenges. This makes the issue relevant in the light of a concrete situation within a time frame that has had a direct impact on increased spending and through reliance on descriptive research methods. The study concluded that Kuwait’s economic challenges depend on oil public revenues, which account for nearly 90% of total public revenues. in addition to some legislative, legal, monetary and financial policy instruments through the Central Bank of Kuwait. The study recommended the development of means to meet economic challenges without relying on public spending and the creation of a parliamentary committee of provisional committees in the National Assembly after each crisis to cooperate with the Government in finding ways to reduce the negative consequences of the crisis.